An Invasive Molar Pregnancy: A Case Report With Associated Imaging. (September 2020) - Levine, Elliot M.; Fernandez, Carlos M.; McElwee, Angela
Human chorionic gonadotropin is generally used as a biomarker to identify invasive molar pregnancy. The extent of the disease (e.g., its staging) has not, however, relied on its sonographic description. A case is presented that can illustrate some diagnostically useful sonographic features of three-dimensional transvaginal sonography for this condition. The clinical imaging of this case initially suggested it to be a benign hydatidiform mole but ultimately was diagnosed as an invasive molar pregnancy, with human chorionic gonadotropin monitoring. Clinical imaging was used to help manage this patient, with the demonstration of trophoblastic invasion of the uterine wall. Although two-dimensional sonography is commonly used to diagnose molar pregnancy, three-dimensional sonography may offer a clinical advantage for the management of invasive molar pregnancy, which can occur in 15% of benign hydatidiform molar pregnancies.